Design and technologies, between sciences and new humanism. Innovation in the education and role of designers - Paris, Spartaco (TECHNE - Journal of Technology for Architecture and Environment, 2021)
Starting from a critical interpretation of some authors involved in the debate raised by the call, this paper hypothesizes practicable conditions for a circular, non-pyramidal integration of technological disciplines into design processes, presenting some experimental investigations in support of these concepts. The paper aims to investigate, in particular, how the role of digital technologies, the key players in a full-blown transformation of thought, impacts the designer’s education models and has a tendency to redefine both the boundaries between disciplines and the very role of the designer. Some significant international experiences in the field of the education of designers show that a humanistic approach to controlling technologies and to “ubiquitous” cooperation among strains of knowledge presents a possible scenario of profound rethinking of the role of the technological designer within a framework of shared fragility of the planet’s economic models.